Solvent effects on the photophysical properties of Bu₄N[(4,40-bpy) Re(CO)₃(bpy-5,50-diCOO)] complex : A combined experimental and computational study - Martínez Saavedra, Héctor Hernando (2016)
The photophysical properties of the complex Bu₄N[(4,4′-bpy)Re(CO)₃(bpy-5,5′-diCOO)] were studied in protic and aprotic media with the aid of steady-state and time-resolved techniques and TD-DFT calculations. The absorption spectrum as well as the steady state and time resolved luminescence of the Re(I) complex display a marked solvent effect. The highest and lowest energy absorption bands experience a bathochromic shift as the polarity of the solvent decreases. In addition, the lowest energy band broadens. Two luminescence bands were observed around 430 and 600 nm in protic organic solvents like alcohols. The high energy emission is observed solely in aqueous solutions, while in aprotic solvents only the low energy luminescence is detected. TD-DFT calculations allowed us to identify the main electronic transitions in the low energy region as ¹MLLCT Re(CO)₃ → 4,4′-bpy and ¹MLLCT Re(CO)₃ → bpy-5,5′-diCOO. The simulated absorption spectra of the Re(I) complex in H2O, protic (EtOH, MeOH) and aprotic (CHCl₃, CH₂Cl₂, CH₃CN) organic solvents follow the experimental absorption spectra with reasonable accuracy both in position and relative intensities. The magnitude of the calculated dipole moment (μ) increases with the dielectric constant of the solvent (εr). Besides, the energy of ¹MLLCT Re(CO)₃ → 4,4′-bpy also increases with εr. However, the energy of the ¹MLLCT Re(CO)₃ → bpy-5,5′-diCOO transition is rather insensitive to εr. This disparity is attributed to the fact that the ¹MLLCT Re(CO)₃ → 4,4′-bpy transition is nearly parallel to the orientation of μ while the ¹MLLCT Re(CO)₃ → bpy-5,5′-diCOO transition is almost perpendicular to it. Unrestricted TD-DFT calculations were successfully applied to the triplet species. It is observed that in the triplet state the Re–N distances are shortened while Re–C distances are elongated relative to the ground state. The calculated emission energy by TD-DFT and/or Δ(SCF) methods was compared to the experimental emission maximum in chloroform. All the experimental results as well as the theoretical calculations indicate that solvent effects on the steady state and time resolved luminescence of the Re(I) complex can be accounted by the coexistence of ³MLLCT Re(CO)₃ → 4,4′-bpy, ³MLLCT Re(CO)₃ → bpy-5,5′-diCOO and ¹IL excited states.